Meditation - Frank Podgorski (Journal of Dharma, 2020)
Our age has been witnessing the resurgence of a great meditation movement, a movement which daily seems to take new forms, gather fresh momentum, and extend its appeal to men and women in all walks of life. What exactly is meditation? Is it a reasoning process, a technique of concentration, a state of altered consciousness unleashing previously untapped energy and potential? Is it just a contemplation of God as the Absolute, or is it a total understanding of the mystery of Self? What do meditators mean by goals described as "ecstasy", absorptive samadbi, intuitive wisdom (prajfia), or the sudden brilliance of satori Enlightenment?